Projetos de Vida de Jovens Estudantes do Ensino Médio e a Escola - Klein, Ana Maria; Arantes, Valeria Amorim (Universidade Federal do Rio Grande do Sul - Faculdade de Educação, 2016)
Abstract: This paper deals with the perception of high school students about the contribution that school experiences can bring to their life projects. We take as references philosopher Ortega y Gasset's concept of design, and that of purpose, as formulated by William Damon. Three hundred and five high school students from the city of São Paulo participated in this study. The qualitative approach (content analysis and formulation of categories) respected the participants' perceptions. The results show that 81% of students believe that the school contributes to their life projects mainly through activities in the classroom.

Resumo: Este artigo trata da percepção de estudantes do Ensino Médio sobre a contribuição que as experiências escolares podem trazer aos seus projetos de vida. Toma-se por referência os conceitos de projeto do filósofo Ortega y Gasset e de purpose, formulado por Willian Damon. Participaram do estudo 305 estudantes do Ensino Médio da cidade de São Paulo. A abordagem qualitativa (análise de conteúdo e formulação de categorias) respeitou as percepções dos participantes. Os resultados demonstram que 81% dos estudantes consideram que a escola contribui para seus projetos de vida, principalmente por meio das atividades desenvolvidas em sala de aula.
Life Projects of High School Young Students and School
Keywords: Youngsters; Life Projects; School Meanings; Jovens; Projetos de Vida; Significados da Escola